Downregulation of E-cadherin in pluripotent stem cells triggers partial EMT - Aban, Cyntia Estefania (2021)
Epithelial to mesenchymal transition (EMT) is a critical cellular process that has been well characterized during embryonic development and cancer metastasis and it also is implicated in several physiological and pathological events including embryonic stem cell differentiation. During early stages of differentiation, human embryonic stem cells pass through EMT where deeper morphological, molecular and biochemical changes occur. Though initially considered as a decision between two states, EMT process is now regarded as a fluid transition where cells exist on a spectrum of intermediate states. In this work, using a CRISPR interference system in human embryonic stem cells, we describe a molecular characterization of the effects of downregulation of E-cadherin, one of the main initiation events of EMT, as a unique start signal. Our results suggest that the decrease and delocalization of E-cadherin causes an incomplete EMT where cells retain their undifferentiated state while expressing several characteristics of a mesenchymal-like phenotype. Namely, we found that E-cadherin downregulation induces SNAI1 and SNAI2 upregulation, promotes MALAT1 and LINC-ROR downregulation, modulates the expression of tight junction occludin 1 and gap junction connexin 43, increases human embryonic stem cells migratory capacity and delocalize β-catenin. Altogether, we believe our results provide a useful tool to model the molecular events of an unstable intermediate state and further identify multiple layers of molecular changes that occur during partial EMT.